2018
DOI: 10.4049/immunohorizons.1800049
|View full text |Cite
|
Sign up to set email alerts
|

The Neuropeptides of Ocular Immune Privilege, α-MSH and NPY, Suppress Phagosome Maturation in Macrophages

Abstract: The ocular microenvironment has evolutionarily adapted several mechanisms of immunosuppression to minimize the induction of inflammation. Neuropeptides produced by the retinal pigment epithelial cells regulate macrophage activity. Two neuropeptides, α-melanocyte–stimulating hormone (α -MSH) and neuropeptide Y (NPY), are constitutively expressed by the retinal pigment epithelial cells. Together these two neuropeptides induce anti-inflammatory cytokine production in endotoxin-stimulated macrophages and suppress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The suppression is in part due to both downregulation of LAMP1, which is needed for phagolysosome acidification, and a blockade of the phagosome maturation pathway preventing the transition of phagosomes from early to intermediate (110). The suppression of phagocytosis and phagosome maturation by the RPE through the neuropeptides a-MSH and NPY would either prevent the processing of antigen within the retina or at least alter the processing of the antigen to unrecognizable amino-acid sequences that could be presented by APC in the retina (110). The RPE from eyes with autoimmune uveitis do not suppress the phagocytic pathway, and this may be associated with high levels of IL-6 expression (105).…”
Section: Rpe and Regulation Of Immunity Rpe Influenced Activity Of Macrophagesmentioning
confidence: 99%
“…The suppression is in part due to both downregulation of LAMP1, which is needed for phagolysosome acidification, and a blockade of the phagosome maturation pathway preventing the transition of phagosomes from early to intermediate (110). The suppression of phagocytosis and phagosome maturation by the RPE through the neuropeptides a-MSH and NPY would either prevent the processing of antigen within the retina or at least alter the processing of the antigen to unrecognizable amino-acid sequences that could be presented by APC in the retina (110). The RPE from eyes with autoimmune uveitis do not suppress the phagocytic pathway, and this may be associated with high levels of IL-6 expression (105).…”
Section: Rpe and Regulation Of Immunity Rpe Influenced Activity Of Macrophagesmentioning
confidence: 99%
“…Besides, co-treatment of RAW264.7 macrophages with melanocyte-stimulating hormone/NPY affects lysosomal activity by inhibiting the expression of lysosomal associated membrane protein 1. This hinders the maturation of phagosomes, but does not affect their antigen presentation function ( 4 ). When treated with NPY only, the phagocytic ability of macrophages to unopsonized Escherichia coli and Staphylococcus aureus biologicals was significantly reduced.…”
Section: Npy Directly Regulates Immune Cellsmentioning
confidence: 99%
“…In the peripheral nervous system, NPY is stored in the postganglionic sympathetic nerve, and co-stored and co-released with norepinephrine (NE) ( 3 ). An increasing number of studies have found widespread existence of NPY in peripheral tissues, such as the retina, smooth muscle, intestine, bone marrow, and thymus ( 4 7 ). Moreover, NPY is also expressed in a variety of immune cells.…”
Section: Introductionmentioning
confidence: 99%
“…α-MSH can suppress both innate immune-mediated and adaptive immune-mediated inflammation [ 124 , 506 , 507 , 508 ]. α-MSH suppresses the production of inflammatory cytokines, ROIs, and NO in macrophages induced by endotoxin, IL-1β, and TNFα [ 502 , 509 , 510 ]. In addition, α-MSH activates suppressor cell activity in macrophages and suppresses the chemotactic activity of macrophages and neutrophils [ 69 , 511 ].…”
Section: Neuropeptides and Their Receptors In The Corneamentioning
confidence: 99%